Analyzing Heavy Metal Levels and Biochemical Indicators in Workers at Local Electrical Generators in Karbala Province of Iraq - Abbas, Rana; Jameel, Hassan; Abbas, Ibtisam (Iraqi Journal of Science, 2026)
Biological materials, such as human blood serum, hair, and nails, are commonly utilized as indicators to assess environmental contamination by heavy metals. The World Health Organization has recommended these biological samples for global ecological monitoring. Concentrations of heavy elemental lead (Pb), cadmium (Cd), and zinc (Zn), as well as oxidative stress markers 8-OHDG, malondialdehyde (MDA), and total antioxidant capacity (T-AOC) were measured in the serum sample. Fingernails and scalp hair were also collected from electrical generator workers of varying ages residing in the Karbala province of Iraq. Atomic absorption spectrophotometers were used to measure the amounts of Cd, Pb, and Zn. Also, 8-OHdG, MDA, and T-AOC were determined using the ELISA method. Data analysis showed significant differences in the average Cd, Zn, and Pb levels in electrical generator workers’ serum, hair, and nails compared to the control groups. The Cd concentration in the worker’s serum measured 4.428 mg/l, while the standard group’s level was 2.590 mg/l. The Cd levels in the worker’s hair were 2.517mg/l. However, the amount in the control group was 0.880 mg/l. The concentration of Cd in the nails of the worker was 1.155 mg/l, and the level for the control group was 0.378 mg/l. The Zn levels for the worker were as follows: 0.849mg/l in the serum, 54.97mg/l in the hair, and 186.6mg/l in the nail. In comparison, the Zn concentrations for the control group were 0.511 mg/l in the serum, 29.12 mg/l in the hair, and 1.209 mg/L in the nail. The results showed a significant rise in the Pb, Cd, and Zn levels in serum, hair, and nails of the workers exposed to the generator’s diesel exhaust fumes in contrast to the control group, highlighting the importance of our study in raising awareness about the consequences of heavy metal pollution for the environment and human health.